ANALISIS STUDI KELAYAKAN BISNIS PADA UMKM DI TINJAU DARI ASPEK PASAR DAN PEMASARAN (STUDI KASUS UMKM CREPES NIHIWATU) - Jeni Fatimatus Sholeha; Febri Ariyantiningsih; Rizkiyah Imri Maulida; Ari Ndururu; Herlina Herlina (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study analyzes the business viability of MSMEs Jinji Dimsum from the perspective of the market and marketing. Crepes, a snack originating from Brittany, France, has attracted the attention of Indonesian society, especially young people. The research method used was qualitative, involving literature studies and marketing strategy analysis. The results show that Crepes has successfully positioned itself as a provider of crepes with a variety of options at an affordable price, as well as an effective marketing strategy through social media. The 4P marketing mix (product, price, promotion, and place) increases brand awareness and expands market reach. In conclusion, this MSMEs business has a large market potential and is viable and worth developing from a marketing perspective.